2010
DOI: 10.1001/archdermatol.2010.328
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis Suppurativa and Concomitant Pyoderma Gangrenosum

Abstract: Background: Hidradenitis suppurativa (HS) and pyoderma gangrenosum (PG) are both rare inflammatory skin conditions that are associated with systemic inflammatory diseases. We performed a retrospective medical chart review of patients with an overlap of HS and PG.Observations: We identified 11 cases of PG lesions presenting in patients with HS. Ten of the patients were women, and 9 were obese. All the patients developed HS lesions first, a median of 2.5 years (range, 0-15 years) preceding the appearance of PG l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
13

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 28 publications
4
77
0
13
Order By: Relevance
“…In HS elevated levels of IL-1 have been demonstrated in lesional and perilesional skin [17]. To date, ten patients have been treated with anakinra with mixed results [88][89][90][91][92]. In seven patients anakinra showed clear improvement of the HS lesions [88,89,92], whereas in the other three patients with severe HS, anakinra was ineffective [90,91].…”
Section: Anakinramentioning
confidence: 99%
“…In HS elevated levels of IL-1 have been demonstrated in lesional and perilesional skin [17]. To date, ten patients have been treated with anakinra with mixed results [88][89][90][91][92]. In seven patients anakinra showed clear improvement of the HS lesions [88,89,92], whereas in the other three patients with severe HS, anakinra was ineffective [90,91].…”
Section: Anakinramentioning
confidence: 99%
“…All patients received multiple therapeutic agents because of ineffective to standard therapies. 11 Reddick et al reported a patient with severe PG associated with HS was respond to adalimumab. 12 In the treatment of PG, the size, depth, growth rate of the lesion, emergence of new lesions, accompanying diseases (inflammatory bowel diseases, arthritis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Pioderma gangrenoso (PG) 28,29 : estudios recientes demuestran una concomitancia clínica de HS y PG en los mismos sitios o en otros diferentes, con ligero predominio en mujeres, con evolución de HS y PG independiente. Las comorbilidades presentes en estos pacientes incluyen acné, artritis, sinovitis, síndrome SAPHO (sinovitis, acné, pustulosis, hiperostosis y osteítis), anemia por deficiencia de hierro, lupus, glomerulonefritis, psoriasis, enfermedad inflamatoria intestinal, enfermedad de Crohn (5%) y enfermedad de Behcet (ocasional).…”
Section: Enfermedades Asociadas a Hidrosadenitis Supurativa 1027 Lasunclassified
“…Hallazgos frecuentes en este grupo son la obesidad, la diabetes mellitus de tipo 2 y la enfermedad arterial coronaria 28 . Se plantea que, tanto la HS como el PG, se deberían a una alteración en la regulación, quimiotaxis, fagocitosis y producción de linfocinas 29 . Recientemente se ha descrito en dos pacientes el síndrome PASH (pioderma gangrenoso, acné e hidrosadenitis supurativa).…”
Section: Enfermedades Asociadas a Hidrosadenitis Supurativa 1027 Lasunclassified